Kinetic evaluation and test–retest reproducibility of [11C]UCB-J, a novel radioligand for positron emission tomography imaging of synaptic vesicle glycoprotein 2A in humans. Issue 11 (November 2018) - Finnema, Sjoerd J; Nabulsi, Nabeel B; Mercier, Joël; Lin, Shu-fei; Chen, Ming-Kai; Matuskey, David; Gallezot, Jean-Dominique; Henry, Shannan; Hannestad, Jonas; Huang, Yiyun; Carson, Richard E
Synaptic vesicle glycoprotein 2A (SV2A) is ubiquitously present in presynaptic terminals. Here we report kinetic modeling and test–retest reproducibility assessment of the SV2A positron emission tomography (PET) radioligand [ 11 C]UCB-J in humans. Five volunteers were examined twice on the HRRT after bolus injection of [ 11 C]UCB-J. Arterial blood samples were collected for measurements of radiometabolites and free fraction. Regional time–activity curves were analyzed with 1-tissue (1T) and 2-tissue (2T) compartment models to estimate volumes of distribution ( V T ). Parametric maps were generated using the 1T model. [ 11 C]UCB-J metabolized fairly quickly, with parent fraction of 36 ± 13% at 15 min after injection. Plasma free fraction was 32 ± 1%. Regional time–activity curves displayed rapid kinetics and were well described by the 1T model, except for the cerebellum and hippocampus. V T values estimated with the 2T model were similar to 1T values. Parametric maps were of high quality and V T values correlated well with time activity curve (TAC)-based estimates. Shortening of acquisition time from 120 min to 60 min had a negligible effect on V T values. The mean absolute test–retest reproducibility for V T was 3–9% across regions. In conclusion, [ 11 C]UCB-J exhibited excellent PET tracer characteristics and has potential as a general purpose tool for measuring synaptic density in neurodegenerative disorders.